DISKURSUS HUSTLE CULTURE DAN EKSPLOITASI KELAS PEKERJA: ANALISIS WACANA KRITIS TERHADAP KOMUNIKASI BISNIS DAN DAMPAK KESEHATAN MENTAL PEGAWAI AGENSI DI JAKARTA SELATAN - Fitria Hani Aprina; Syfa Amelia; Agnes Monica Marpaung; Deanda Dewindaru; Lailatus Sholihah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study examines the phenomenon of hustle culture and the mental health crisis among young workers (Generation Z and Millennials) in the urban creative industry sector, with a geographical focus on South Jakarta. Employing a qualitative approach through a critical literature review design and critical discourse analysis, this study dismantles the structural narratives that reproduce labor exploitation in the era of digital capitalism. The analysis reveals three main findings. First, at the macro level, the Job Creation Law (UU Cipta Kerja) regime and the absence of the Right to Disconnect create a legal protection vacuum that locks workers into permanent precarity. Second, within corporate power relations, the jargon of flexibility and the commodification of passion are utilized to manipulate extreme exhaustion as dedication, to which young workers respond through passive resistance such as quiet quitting and mass resignation intentions. Third, geographically, the South Jakarta agglomeration area operates as an incubator for social pathology, evidenced by a private worker burnout syndrome rate reaching 40.3% and a youth emotional disorder prevalence of 11.26%. This study concludes that the mental health crisis in the digital industry is a product of structural exploitation, not an individual psychological resilience weakness, thus demanding radical intervention through labor law restructuring.